Análisis termo-económico de un esquema tecnológico para la producción de etanol por su destilación extractiva (2019)
Fuel ethanol is a biofuel of great interest today, which is why the market has evolved to produce this biofuel more cheaply, this is where thermoeconomics is applied, making a thermoeconomic analysis to a simulated technological scheme in ASPEN PLUS ® in its version 9.0; It is possible to perform this analysis and quantify exergy and thermoeconomic prices for each of the currents present in the system, in parallel performing an exergy analysis for the quantification of lost work and thus obtaining the cost of exergy loss. The methodology developed to perform thermoeconomics is taken from the literature and divided into 4 important steps, the exergy analysis or second law availability, taking into account the balance of the environment, the economic analysis quantified by the correlations for specialized distillation found by means of a bibliographic review, the quantification of exergy costs to know the cost of useful energy, and finally with a balance of inputs / economic, determine the thermoeconomic cost for each current present. Having said analysis, the system is optimized by means of an indirect objective function that relates the amount of heat supplied per mole of distillate produced under the restrictions of anhydrous ethanol and an ethanol outlet for funds not greater than 0.2% on a molar basis . By optimizing the process, it was possible to find out which parameters such as the investment by CT and the entropy generated are minimized and with this the cost of exergy loss.